Rancang Sistem Kamus Hukum Untuk Aplikasi Android - Nia Ekawati; Rizki Tri Anugrah Bhakti (Prosiding, 2018)
The legal environment is divided into two parts of criminal law and civil law. Based on these two parts there are some terms of foreign terms that are used, but not necessarily the legal person himself who just started learning will quickly remember it. The legal dictionary application helps legal people who are new to learning foreign terms in legal language, with the design process helping the application process in a more detailed direction. In addition, it helps practitioners in the practical legal environment use it, by looking at one application all the required data or information can be searched. The tools of this legal dictionary app are smartphones or smartphone smartphones that are more popular in the community as smartphones. Smartphones are now very close to the communication needs of all people, so the design of the application in the future does not rule out the possibility of being able to be used through Android-based smartphone phones. The formulation of the problem in this research is how to design a legal dictionary system with the help of android application. While the purpose of this study is to design a legal dictionary system with the help of an android application. Based on the results of the research design of a legal dictionary system, then with the help of an android application can help people who are less aware of the system can understand the workings of the system in detail. Starting from the initial view to how to find data on the dictionary.